Effects of Microlearning Based Science Modules on Conceptual Understanding and Self Regulated Learning: A Quasi Experimental Study in Senior Secondary Schools - Hamdani Hamdani; Reni Marlina; Nurussaniah; Suci Siti Lathifah; Aminah Zb (International Journal of Education and Teaching Zone, 2026)
This study examined the effectiveness of a microlearning-based science module in enhancing students' conceptual understanding and self-regulated learning (SRL). Employing a quasi-experimental non-equivalent control group design, 32 secondary students were equally assigned to experimental (microlearning) and control (conventional instruction) groups. Data were collected through validated conceptual understanding tests, SRL questionnaires, and delayed post-tests to measure retention. Descriptive results showed the experimental group consistently outperformed the control group across all measures, achieving higher mean scores in conceptual understanding (M = 81.38, SD = 6.41 vs. 72.06, SD = 6.87), SRL (M = 82.25 vs. 71.81), and retention (M = 78.94 vs. 69.13). Inferential analysis revealed significant differences in overall conceptual understanding (t = 3.21, p = 0.003) with a large effect size (Cohen's d = 0.80), as well as across specific indicators of basic concepts, conceptual application, and scientific reasoning. These findings indicate that microlearning effectively supports deeper conceptual understanding, learner autonomy, and long-term retention by reducing cognitive load and enabling flexible, self-paced learning, positioning it as a promising instructional approach for strengthening science education quality at the secondary level.